AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols and aldehydes: enabling the diastereoselective synthesis of [6,6,6]-trioxa-fused ketals and hexahydro-2H-chromenes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2025)
We report the unprecedented diastereoselective synthesis of novel [6,6,6]-trioxa-fused ketals via AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols (with primary or secondary hydroxyl groups) and aldehydes through a [2+2+1+1] pathway. In contrast, 5-hexyn-1-ols with tertiary hydroxyl groups yield hexahydro-2H-chromenes via a [3+1+1+1] pathway.